CENTRAL ASIAN AND CAUCASIAN STRATEGY: SEVERAL MODELS OF INTERRELATIONS AMONG THE U.S., CHINA, AND RUSSIA - IGITALIEV, Shukhratzhon; KARIMOVA, Albina (CENTRAL ASIA AND THE CAUCASUS, 2007)
Several development trends in global policy have stabilized recently, which makes it possible to put forward certain hypothetical models of interrelations among such major players in international relations as the U.S., Russia, and China. In turn, by creating models of the interrelations among these states at the global level, certain conclusions can be drawn that are beneficial for drawing up the paradigms of Washington’s, Moscow’s, and Beijing’s Central Asian and Caucasian strategies. This article makes an attempt to analyze certain aspects of this problem, taking into account the growing urgency of issues relating to cooperation among the indicated powers within the framework of their foreign policy strategy in Central Asia and the Caucasus. For example, the results of this study, which was conducted by means of a factorial and comparative analysis, make it possible to forecast the appearance of a new conception of world order in the near future, in which the balance will tilt in favor of U.S.- PRC interaction, while Russia will be pushed into the background. For example, the results of the analysis show that the model of the declared strategic U.S.-Russia partnership is disintegrating and the U.S.-PRC dialog is gaining momentum in the face of the rise in Russia’s demonstrative strategic support of the Islamist forces on the international arena. Moscow is thus trying to establish strategic interaction with the mentioned forces, which the Kremlin regards as its most “efficient” partners in counterbalance to the U.S. (and possibly to the PRC in the future) on the global scene.